2019
DOI: 10.14716/ijtech.v10i4.668
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors (CSFS) In University-Industry Collaboration (UIC) Projects in Research Universities

Abstract: No Success Factors References 1 Champion at company (Claes Wohlin, 2012) 2 Champion's network within the company (Claes Wohlin, 2012) 3 Buy in and support from company management (Claes Wohlin, 2012) 4 Buy in and support from industry collaborators (Claes Wohlin, 2012) 5 Short term results and impact on industry (Claes Wohlin, 2012) 6 Organizational stability (industry partner) (Claes Wohlin, 2012) 7 Researcher has a visible presence in industry (Claes Wohlin, 2012) 8 Regular meetings (Claes Wohlin, 2012) 9 Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In response to this issue, technology and university-industry collaborations need to be employed (Hanid et al, 2019;Berawi et al, 2020). In conjunction with industrial partners, our institution designed and manufactured a locally made nasopharyngeal swab called "Dacron Swab HS 19," using food-grade resin material and flocked fiber.…”
Section: Introductionmentioning
confidence: 99%
“…In response to this issue, technology and university-industry collaborations need to be employed (Hanid et al, 2019;Berawi et al, 2020). In conjunction with industrial partners, our institution designed and manufactured a locally made nasopharyngeal swab called "Dacron Swab HS 19," using food-grade resin material and flocked fiber.…”
Section: Introductionmentioning
confidence: 99%
“…However, further work to locate the brain tumor position more precisely using the average subtraction method is possible. The purpose of forming this industry (CTECH Labs EdWar Technology) and university (University of Muhammadiyah professor Dr. HAMKA) collaboration is to ensure success (Hanid et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A study based on the perspectives of industry players and academicians on the success factors however, showed diverse results. Although industrial players considered effective communication between partners as the most important factor in determining a successful university-industry collaboration, university researchers were of the view that other factors such as teamwork, leadership, and financial support were the crucial elements of success (Hanid et al, 2019).…”
Section: Factors Contributing Towards Successful University-industry Collaborative Projectmentioning
confidence: 99%
“…This means that communication is not an important factor to consider in developing a successful collaboration. Hanid et al (2019) indicated that in some cases, when the collaboration partners were committed and fulfilled their responsibility since the beginning of a project, conducting regular meetings was not compulsory. As indicated by Ndudzo and Zinyama (2014), good communication skills were required in order to develop successful collaboration projects.…”
Section: Factors Contributing Towards Successful University-industry Collaborative Projectmentioning
confidence: 99%
See 1 more Smart Citation